Twórczość literacka internowanych w czasie stanu wojennego (1981–1983) - Orman, Kamila (Acta Universitatis Lodziensis. Folia Historica, 2013)
Introduction of the martial law in Poland on 13 December 1981 met with a strong public resistance. A popular form of protest was occasional poetry . To a great extent it was created by political internees. By placing internees’ poetry in the context of social events which took place during the time of martial law we can prove its great functional value. Undeniable advantage of this literary output is the record of the experience of isolation. There is nothing more elusive than the way in which human emotions and experiences are expressed. The occasional poetry played also a particular role in a political discourse of that time. Its aim was to continue the process of purifying the language from newspeak, defense of internees and oppressed and discrediting actions of authorities. Also diaries and memoirs were also created in detention centers. The literary output of internees constitutes a document of awareness of this social group. Thanks to this literature we can learn about arrests, the reality of everyday life in detention centers, relations between internees and guards, forms of repression, problems faced by internees, their emotions and results of isolation.